Transformasi Layanan Bimbingan dan Konseling di Era Digital: Sebuah Tinjauan Literatur tentang Peluang dan Tantangan Praktik - Siti Muafanah (PT. PENERBIT TIGA MUTIARA, 2026)
The transformation of guidance and counseling services in the digital era has brought significant changes to the ways counselors deliver services to students. Advances in information and communication technology have created both opportunities and challenges that require comprehensive scholarly examination. This study aims to analyze the opportunities, challenges, and implications of digital transformation for the development of guidance and counseling practices. A qualitative approach was employed through a Systematic Literature Review of scholarly articles published between 2016 and 2026. The data were analyzed using content analysis and thematic analysis to identify key themes related to digital guidance and counseling services. The findings reveal that digital technologies enhance service accessibility, flexibility, and effectiveness, while also fostering innovation through the utilization of digital applications and artificial intelligence. Nevertheless, the transformation continues to face challenges, including counselors’ limited digital competencies, barriers to virtual therapeutic communication, and concerns related to ethics, privacy, and data security. The study concludes that a hybrid service model integrating face-to-face counseling with digital counseling represents the most appropriate approach for addressing students’ needs in the digital era. The novelty of this study lies in its comprehensive synthesis that integrates technological dimensions, counselor competencies, professional ethics, data security, and humanistic approaches as a foundation for the development of effective and sustainable digital guidance and counseling services.